The Use of TGT Cooperative Learning for Chemistry Learning on Tenth-Grade Students - Agustina, Nika Rosa; Priscylio, Ghery; Rachman, Fuad Abd; Effendi, Effendi (Unnes Science Education Journal, 2020)
This study aims to improve student learning outcomes on chemistry subjects by applying the Teams Games Tournament (TGT) learning model for tenth-grade students. The method used is classroom action research that is carried out in three cycles, each cycle consisting of two meetings. Techniques of data collecting use the observation sheet and final testing cycle. Observation sheet was used to determine the activity of students and the test to determine student learning outcomes. Based on research, gained mastery learning outcomes of students increased from 45% before treatment (T0) to 55% in the first cycle (T1), 72.5% in the second cycle (T2) and 87.5% in the third cycle. Average student activity within the group at the first cycle of 53.43%, 57.18% for the second cycle and the third cycle of 64.47%. Average student learning outcomes at the first cycle of 70, 55, 72,125 for the second cycle and the third cycle of 74,6. Cooperative learning strategies are effective when the curricular knowledge taught in the school is drawn from all groups by playing. Based on these results, the researchers suggest to teachers who have the same problem in learning can apply learning model Teams Games Tournament (TGT).